PENGARUH LINGKUNGAN SEKOLAH TERHADAP KONSENTRASI BELAJAR PESERTA DIDIK DI MAS BABUSALAM SIMANDOLAK KECAMATAN BENAI KABUPATEN KUANTAN SINGINGI - Ulfa Novrilla; Andrizal Andrizal; Zulhaini Zulhaini (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2020)
The influence of the school environment on the concentration of student learning in MAS Babusalam Simandolak. This research is motivated by the lowconcentration of student learning, because the school environment is located on the side of the road, and there is a kindergarten next to MAS Babusalam which makes it difficult for students to concentrate. The purpose of this study was to determine the effect of the school environment on student concentration. The study was conducted by all participants inMAS Babusalam Simandolak, with a total poplation of 25. Techniques sed to collect data in the field were observation, interviews, questionnaires and documentation. So the significant value (sig) is 0.0328 and the probability value (sig) is 0,05%. Then the sig value is smaller than the probability with the following equation : 0.0328 > 0.05 means that there is no influence of variable x on the variable y. Based on the value of the output above t count is 0.999 and t table is 2.069 and the conclusion is t count 0.999 < t table 2.069 so ha is rejected ho is accepted, then there is no influence between the school environment on student concentration. It can be seen that the determination value R2 (R square) is 0.042, this means that the school environment determines as much as 4.2% of the concentration of student learning while the remaining 95.8% is influenced by other variables not examined by this researcher.